Functionalization of electrospun poly(ε-caprolactone) scaffold with heparin and vascular endothelial growth factors for potential application as vascular grafts. (March 2013) - Wang, Zhexiang; Sun, Bin; Zhang, Min; Ou, Lailiang; Che, Yongzhe; Zhang, Jun; Kong, Deling
In this study, a heparin-conjugated poly(ε-caprolactone) electrospun fiber was constructed to develop a functional scaffold for controlled release of vascular endothelial growth factors. The immobilization of vascular endothelial growth factor was achieved through affinity binding between heparin and vascular endothelial growth factor molecules. The sustained release of vascular endothelial growth factor from the scaffold was followed for up to 15 days. The endothelial cell adhesion and proliferation assay demonstrated that immobilized vascular endothelial growth factor maintained its activity. The blood compatibility of the scaffold was evaluated by activated partial thromboplastin time, platelet adhesion test, and arteriovenous shunt, and the functionalized scaffold showed improved anticoagulation properties. The biocompatibility was evaluated by subcutaneous implantation. Results showed that this vascular endothelial growth factor–releasing scaffold stimulated neovascularization with minimum immunological rejection compared to the unmodified poly(ε-caprolactone) scaffold. The present study demonstrated a new strategy of building bioactive scaffolds for the development of small-diameter vascular graft.